Pengaruh Kualitas Produk, Lokasi Dan Tata Letak Terhadap Keputusan Pembelian Pada Super Indo Tlogomas (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis) - Salman AL Farizy; Eka Farida; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract  This study aims to determine and analyze the influence of product quality, location and layout on purchasing decisions at Super Indo Tlogomas. The type of approach taken is a quantitative approach. With the type of explanatory research. The population in this study is students of the faculty of economics and business. The samples used in this study were 95 samples. The data used is primary data using questionnaires. The data analysis methods used are instrument tests: validity and reliability tests, normality tests, classical assumption tests: multicollinearity tests and heteroscedasticity tests, multiple linear regression analysis, hypothesis tests: simultaneous tests, partial tests and coefficients of determination. From the results of the study simultaneously obtained the results that product quality, location and layout have a significant effect on purchasing decisions. Product quality has a significant positive effect on purchasing decisions. Location has a significant positive effect on purchasing decisions. The layout has a positive insignificant effect on purchasing decisions. Keywords: Product Quality, Location, Layout and Purchasing decision.